EU cohesion policy in the light of Lisbon and Gothenburg objectives: The case of Italy - COTELLA, Giancarlo (Discussion Papers, 2011)
Cohesion policy became a cornerstone of the European Union (EU) with the adoption of the Single European Act in 1986, aiming at balancing out the economic and social disparities between the richest and poorest regions in the Community and to promote further economic integration. In the meantime, the EU adopted the Lisbon strategy (EC, 2000) with a view to turning Europe into a competitive knowledge economy, further complemented by the Gothenburg European Council that emphasised the role of the three pillars of sustainability (economic, social and environmental). Since the adoption of the Lisbon and Gothenburg Agendas, many of the instruments characterising the Structural Funds’ programming periods tried to cope with the challenges to integrate the new dimensions and priorities into EU cohesion policy. Nevertheless, no explicit link between 2000–2006 regional policy and Lisbon and Gothenburg goals was made, mostly due to the fact that the rationale behind the definition of the programming period obeyed to logics developed at the end of the 1990s, in other words before the approval of the two documents. The 2007–2013 programming period has been pivoted on the recommendations of the spring 2005 European Council, stressing the need for better linkage between the Lisbon/Gothenburg strategies and Cohesion policy. Despite the fact that the strategic dimension of Cohesion policy has been strengthened to ensure a higher integration of Community priorities into domestic development programmes, the Lisbon and Gothenburg agendas continue to challenge traditional approaches to policy making as there is no single policy mechanism that can ensure their successful implementation. The present paper aims at shedding some light on this issue, exploring the potential for Italy’s European Regional Development Fund (ERDF) policy instruments 2007–2013 to contribute to the Lisbon and Gothenburg objectives for growth, jobs and sustainable development. Drawing on previous research conducted by the author, the contribution starts by introducing the general context for regional policy in Italy, briefly describing the challenges characterising the national territory as well as the framework for 2007–2013 regional policy and the resources dedicated to it. It then focuses on the way Lisbon and Gothenburg priorities are taken into account in the different programmes at the different territorial levels. A final section rounds off the contribution, providing a set of conclusive remarks on the effective potentials of Italian Regional policy 2007–2013 to contribute to the Lisbon/Gothenburg strategy, and positioning Italy’s specific ‘road to Lisbon’ within the broader EU framework.